2017
DOI: 10.1371/journal.pone.0180469
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the CCCH zinc finger family identifies tissue specific and stress responsive candidates in chickpea (Cicer arietinum L.)

Abstract: The CCCH zinc finger is a group of proteins characterised by a typical motif consisting of three cysteine residues and one histidine residue. These proteins have been reported to play important roles in regulation of plant growth, developmental processes and environmental responses. In the present study, genome wide analysis of the CCCH zinc finger gene family was carried out in the available chickpea genome. Various bioinformatics tools were employed to predict 58 CCCH zinc finger genes in chickpea (designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Cysteine-cysteine-cysteine-histidine (CCCH) zinc-finger proteins usually possess one to seven copies of CCCH motifs, which are newly defined as C-X 4–17 -C-X 4–6 -C-X 3 -H [ 5 , 6 , 7 ]. CCCH genes are widely distributed in organisms from bacteria to eukaryotes [ 5 , 8 ], and members of this gene family in various plants have also been predicted in silico [ 5 , 6 , 7 , 9 , 10 , 11 , 12 ]. For instance, 68 CCCH-type zinc-finger protein genes divided into 11 subfamilies have been identified in the Arabidopsis thaliana genome [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine-cysteine-cysteine-histidine (CCCH) zinc-finger proteins usually possess one to seven copies of CCCH motifs, which are newly defined as C-X 4–17 -C-X 4–6 -C-X 3 -H [ 5 , 6 , 7 ]. CCCH genes are widely distributed in organisms from bacteria to eukaryotes [ 5 , 8 ], and members of this gene family in various plants have also been predicted in silico [ 5 , 6 , 7 , 9 , 10 , 11 , 12 ]. For instance, 68 CCCH-type zinc-finger protein genes divided into 11 subfamilies have been identified in the Arabidopsis thaliana genome [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies indicated that C3H genes were involved in various development stage and different stress response. For example, previous studies revealed that CarC3H26 and 51 had higher expression during early stages of chickpea seed development (Pradhan et al, 2017). In rice, OsC3H33, OsC3H37 and OsC3H50 were induced by salt stress (Muhamman, Waqas & Asia, 2010).…”
Section: Excellent Candidates For Salt-tolerance Improvementmentioning
confidence: 98%
“…The C3H members play important roles in plant response to the environment. A number of researchers have elucidated the association of C3Hs with diverse plant growth regulatory processes via genome-wide analysis in Arabidopsis and rice (Wang et al, 2008), poplar (Chai et al, 2012), maize (Peng et al, 2012), switchgrass (Yuan et al, 2015), alfalfa (Zhang et al, 2013), citrus (Liu et al, 2014), tomato (Xu, 2014), grape vine (Wang, Zhong & Cheng, 2014), chickpea (Pradhan et al, 2017), banana (Mazumdar et al, 2017) and cabbage (Rameneni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence suggests that CCCH (C3H) as a novel type Znf transcription factors regulate gene expression by binding on targets genes mRNA [7][8][9]. To verify its characteristics, based on the genome-data, the comprehensive analysis of C3H Znf family was performed in dicotyledonous Arabidopsis thaliana [9], Medicago truncatula [10], Populus trichocarpa [11], Clementine mandarin [12], Vitis vinifera [13], Cicer arietinum [14], monocotyledonous Musa acuminata [15], Zea mays [16], and Oryza sativa [9] , showed that C3H Znf family widely involved in biotic and abiotic pathways. Besides, C3H Znf members have various functions.…”
Section: Introductionmentioning
confidence: 99%